2011
DOI: 10.1118/1.3592933
|View full text |Cite
|
Sign up to set email alerts
|

An empirical model of diagnostic x‐ray attenuation under narrow‐beam geometry

Abstract: The proposed Lambert W model accurately describes attenuation of both monoenergetic radiation and (kilovoltage) polyenergetic beams (under narrow-beam geometry).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Figure 2 shows the experimental setup for the nonrotating method. In the service engineering mode, the X‐ray tube was positioned at 6 o'clock direction, the ionization chamber was placed free‐in‐air at the isocenter of the gantry, (1,4) and the aluminum filters were placed on a 25 mm wide lead collimator 75 mm above the bottom surface of the gantry.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the experimental setup for the nonrotating method. In the service engineering mode, the X‐ray tube was positioned at 6 o'clock direction, the ionization chamber was placed free‐in‐air at the isocenter of the gantry, (1,4) and the aluminum filters were placed on a 25 mm wide lead collimator 75 mm above the bottom surface of the gantry.…”
Section: Methodsmentioning
confidence: 99%
“…The Lambert-W function has applications in various scientific disciplines, and recently it has been utilized in modeling of kilovoltage x-ray beam attenuation. 16 It will be shown that the proposed model has a computational complexity far less compared with the existing methods and provides a close match to the gold standard modeling techniques, such as MC simulation.…”
Section: Introductionmentioning
confidence: 92%
“…whose solution involves the Lamber-W function (readers are advised to refer to Appendix A of 16 ) given by E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 2 0 ; 6 3 ; 5 6 6 I ¼…”
Section: Generalized Beer-lambert Law (Proposed Model)mentioning
confidence: 99%
See 1 more Smart Citation
“…Appendix: Excluding the model by Mathieu et al 31 proposed an attenuation model based on the Lambert W function. According to this model the measured intensities should be described by the following equation: However, our data clearly deviate from eq.…”
Section: Acknowledgmentsmentioning
confidence: 99%